Mean Platelet Volume and Immature Platelet Fraction in Autoimmune Disorders - Schmoeller, Deonilson; Picarelli, Maria Mercedes; Paz Munhoz, Terezinha; Poli de Figueiredo, Carlos Eduardo; Staub, Henrique Luiz (Frontiers in Medicine, 2017)
The mean platelet volume (MPV), available in automated blood analyzers, has been considered as a potential biomarker in cardiovascular disease, diabetes mellitus and cancer. This test, which is a useful tool in the differentiation of thrombocytopenic states, has now been evaluated in autoimmune disorders, though data is yet scarce. Current information account for a controversial role of MPV as a biomarker of systemic and organ-specific autoimmune disorders. Another test, the immature platelet fraction (IPF) measures the number of young, reticulated platelets. Obtained by automated hematology analysis or flow cytometry, there is an elevation of IPF in patients with rapid platelet destruction. This test has been seldom studied in autoimmune diseases. Standardization of a cutoff value is a chief necessity for both MPV and IPF. In this review, we focus on the current applicability of MPV and IPF as biomarkers in patients with autoimmune disorders.